ISOLATION AND SPECIATION OF CANDIDA FROM LEUCORRHOEA SAMPLES OF REPRODUCTIVE AGE WOMEN WITH ANTIFUNGAL SUSCEPTIBILITY OF THE ISOLATES - YASODA DEVI KAKARAPARTHI; VIJAYA KUMAR PUNNAPU; SWATHI KUNA; LAKSHMI MOUNIKA ADDANKI (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: (1) To isolate and identify Candida species from leucorrhoea samples of women aged 15–45 years. (2) To determine the distribution of Candida species. (3) To evaluate the antifungal susceptibility of the isolates. Methods: A cross-sectional, descriptive study was conducted from October 2018 to January 2020 at King George Hospital and Andhra Medical College, Visakhapatnam. 259 high vaginal swab samples were collected from women with leucorrhoea symptoms. Direct microscopy and culture on Sabouraud’s dextrose agar were used for Candida isolation. Species identification involved standard biochemical tests, including the germ tube test, cornmeal agar, HICHROME agar, and sugar assimilation/fermentation tests. Antifungal susceptibility was assessed using the disc diffusion method for six antifungals: amphotericin B, clotrimazole, fluconazole, itraconazole, ketoconazole, and nystatin. Results: Out of 259 samples, 100 Candida isolates (38.6% prevalence) were obtained. The most affected age group was 31–35 years (34%), followed by 21–25 years (27%). Non-albicans Candida (NAC) species (59%) were more prevalent than Candida albicans (41%). Among NAC species, Candida glabrata (23%) and Candida tropicalis (19%) predominated. All Candida isolates were 100% susceptible to amphotericin B and nystatin. C. albicans demonstrated the highest resistance to fluconazole (26.9%). Among NAC species, Candida krusei exhibited 100% resistance to fluconazole and significant resistance to other azoles. Conclusion: The study reveals a rising trend in NAC infections with higher antifungal resistance. Amphotericin B and nystatin remain the most effective treatments. Early species-specific identification and antifungal susceptibility testing are essential to guide appropriate therapy and curb emerging antifungal resistance. Further research is required to establish regional Candida epidemiology and optimize empirical treatment guidelines.